OPTION TO PREVENT RADIATION CYSTITIS - Zhukova, T.A.; Vasko, L.N.; Pocherniayeva, V.F.; Sokolova, N.A.; Kornyeyev, O.V. (World of Medicine and Biology, 2019)
External Beam Radiation Therapy (EBRT) is an efficient method of treatment for many types of tumors. But with different approaches, fields, and combinations of doses, the bladder lesions are inevitable. Therefore, one of the priority unsolved issues in the present day radiology is the issue of prevention and control of radiation reactions and injuries. The purpose of the present study was to develop a method for the prevention and treatment of radiation reactions in the treatment of patients with bladder cancer receiving gamma-ray teletherapy (GRT) and to substantiate the antioxidant and reparative role of the Emoxypin drug in this pathology. The severity of radiation reactions in patients receiving radiation therapy in the usual fractionation mode and with multi-fractionation of dose was under study. The total of 27 patients participated in the observation, those with bladder cancer diagnosed and subjected to the EBRT on the definitive treatment program. Analyzing the results obtained, it can be noted that the use of EBRT in the mode of the daily dose multifraction reliably (p = 0.05) reduces the reaction of the bladder mucosa. Thus, the reactions of the 3rd degree (ulcerative) differ by 4.31 times in favor of group II (experimental) where the mode of multifraction and the Emoxypin drug was used. Reactions of the 2nd degree (erosive-desquamated) differ by 1.24 times and also favor group II, but this indicator is unreliable. Reactions of 1 degree (catarrhal) differ by 3.72 times, which has a sufficient reliability in favor of the treatment performed in the patients of group II. The effect of bladder installations in patients with radiation cystitis, complicated with an infectious process, compared with the traditional methods of therapy, permitted to reduce the term of patients’ stay in hospital by 6-7 days.
Keywords: bladder cancer; antioxidants; remote gamma therapy; radiation reactions; radiation injury; cystitis